A kind of bending-resistant acrylic film and its preparation method and application

By using a combination of low Tg high molecular weight acrylate resin A and high Tg low molecular weight acrylate resin B, combined with the ultraviolet polymerization process, a bend-resistant acrylate film with excellent bending performance and good recovery performance was prepared, which solved the problem that it is difficult to meet the bending performance and creep recovery requirements of flexible folding OCA in the prior art.

CN119371908BActive Publication Date: 2025-05-02KUNSHAN BYE MACROMOLECULE MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411912901.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-05-02
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the bending resistance of flexible folding OCA under 200,000 folding conditions, while meeting the requirements of low-temperature modulus stability, good bonding characteristics and excellent creep recovery.

Method used

By using a combination of low Tg high molecular weight acrylate resin A and high Tg low molecular weight acrylate resin B, combined with an ultraviolet polymerization process and an appropriate crosslinking agent and a photoinitiator, a bending-resistant acrylate film with excellent bending performance and good recovery performance was prepared.

Benefits of technology

It achieves bending resistance without crease or damage under 200,000 folding conditions, and has good bonding characteristics and creep recovery effect to meet the needs of dynamic folding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371908B_ABST
    Figure CN119371908B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of adhesive films, and in particular to a bending-resistant acrylic adhesive film, which comprises an acrylic resin A, an acrylic resin B, a photoinitiator C and a crosslinking agent D; wherein the weight average molecular weight Mw of the acrylic resin A is 700,000-1.2 million; the weight average molecular weight Mw of the acrylic resin B is 3000-10000, and the glass transition temperature Tg of the acrylic resin B is 30°C-70°C. The acrylic adhesive film provided by the present invention has high adhesion to a substrate and good creep recovery, and can be applied in the field of flexible OLED displays to meet the stringent bending resistance requirements of foldable mobile phones.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of display technology, and in particular to a bending-resistant acrylic film and a preparation method and application thereof. Background Art

[0002] The application of optically clear adhesive (OCA) in consumer electronic products such as smartphones and tablets is increasing. As people's requirements for screen clarity and touch experience continue to increase, the demand for OCA optical adhesive is also growing. Foldable electronic devices need to be equipped with foldable displays, and the display needs to use adhesives to fix the various components in its structure, so the development of flexible folding OCA is gradually emerging. Flexible folding OCA needs to meet the requirements of at least ensuring that the product will not be creased or damaged under 200,000 folding conditions. At the same time, OCA must meet the requirements of modulus stability, good bonding properties, and excellent creep recovery in the temperature range of -30°C to 80°C.

[0003] Patent CN118006261A points out that adding too much polar monomer will cause gel problems, and adding Tg monomers with high nitrogen content will significantly increase the low-temperature modulus, which is not conducive to low-temperature folding performance; the increase of oligomers will cause compatibility problems, and the modulus will also decrease rapidly at high temperatures, resulting in poor high-temperature performance.

[0004] Patent CN116745380A proposes that in a low temperature environment, the adhesive film is required to have excellent bending properties. By using acrylate oligomers, the adhesive properties, bending properties, etc. are adjusted, but the addition of acrylate oligomers will cause compatibility problems and fail to meet the optical performance requirements.

[0005] Patent CN108064202A uses isooctyl acrylate, hydroxybutyl acrylate, dodecyl acrylate, etc., which are polymerized into a coatable viscosity under low light intensity. Although adding a large amount of long side chain alkyl chain monomers can reduce the storage modulus at low temperatures, adding too much will reduce the adhesion to the substrate.

[0006] In recent years, flexible devices such as foldable devices and rollable devices have been developed for use in various environments, requiring the film to have excellent bending properties while meeting requirements such as storage modulus and good peel strength. In the traditional solution method for synthesizing foldable OCA, the free radicals generated by the thermal initiator are transferred to the solvent, so it is difficult to obtain a high molecular weight product. The use of UV polymerization to synthesize foldable OCA can obtain a high molecular weight product, but the molecular weight distribution PDI of the film is less than 2, the molecular weight distribution of the film is narrow, and the peeling force on the substrate is low. Summary of the invention

[0007] In view of the above-mentioned shortcomings of the prior art, the present invention provides a bending-resistant acrylic film, which exhibits excellent bending performance and good recovery performance, has high adhesion to the substrate, and can meet the stringent bending resistance requirements of foldable mobile phones.

[0008] Technical solution:

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0010] In a first aspect, the present invention provides a bending-resistant acrylic film, which includes an acrylic resin A, an acrylic resin B, a photoinitiator C and a cross-linking agent D;

[0011] The weight average molecular weight Mw of the acrylic resin A is 700,000-1.2 million; the weight average molecular weight Mw of the acrylic resin B is 3,000-10,000; and the glass transition temperature Tg of the acrylic resin B is 30° C. to 70° C.

[0012] Preferably, the weight average molecular weight Mw of the acrylate resin A is 800,000-1,000,000; the solid content of the acrylate resin A is 7-25%, and the viscosity is 1,500-10,000 cps; the weight average molecular weight Mw of the acrylate resin B is 3,000-8,000, and the glass transition temperature Tg of the acrylate resin B is 30-55°C.

[0013] Preferably, a bending-resistant acrylic film is provided, wherein the raw materials for preparing the acrylic film include, by weight: 100 parts of acrylic resin A, 0.1-10 parts of acrylic resin B, 0.01-1 parts of photoinitiator C, and 0.01-1 parts of crosslinking agent D.

[0014] More preferably, a bending-resistant acrylic film is provided, wherein the raw materials for preparing the acrylic film include, by weight: 100 parts of acrylic resin A, 3-10 parts of acrylic resin B, 0.1-1 parts of photoinitiator C, and 0.01-0.5 parts of crosslinking agent D.

[0015] Most preferably, a bending-resistant acrylic film is provided, wherein the raw materials for preparing the acrylic film include, by weight: 100 parts of acrylic resin A, 5-10 parts of acrylic resin B, 0.1-0.5 parts of photoinitiator C, and 0.01-0.1 parts of crosslinking agent D.

[0016] Most preferably, a bending-resistant acrylic film is provided, wherein the raw materials for preparing the acrylic film include, by weight: 100 parts of acrylic resin A, 5-10 parts of acrylic resin B, 0.3 parts of photoinitiator C, and 0.06 parts of crosslinking agent D.

[0017] In the above-mentioned bending-resistant acrylic film, the crosslinking agent D is at least one of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate, and bifunctional aliphatic polyurethane acrylate. The amount of the crosslinking agent D used is generally about 0.01 to 1 part by weight, preferably 0.01 to 0.5 part by weight, relative to 100 parts by weight of the acrylic resin A.

[0018] In the above-mentioned bend-resistant acrylic film, the photoinitiator C is at least one or more of 1-hydroxycyclohexyl phenyl ketone, (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, a,a-dimethoxy-a-phenyl acetophenone, and benzil dimethyl ether.

[0019] The acrylic resin A is prepared by an ultraviolet polymerization process, wherein 30-75 parts by weight of an acrylic monomer having 4-8 carbon atoms, 5-40 parts by weight of an acrylic monomer having 8-17 carbon atoms, 5-20 parts by weight of a hydroxy acrylic monomer, 0-5 parts by weight of a nitrogen-containing group acrylic monomer, 0.01-0.5 parts by weight of a chain transfer agent and 0.01-1 parts by weight of a polymerizable photoinitiator are partially polymerized under ultraviolet light.

[0020] Preferably, the acrylic resin A is prepared by ultraviolet polymerization process, wherein 40-70 parts by weight of acrylic monomers having 4-8 carbon atoms, 10-40 parts of acrylic monomers having 8-17 carbon atoms, 5-14 parts of hydroxy acrylic monomers, 0-3 parts of nitrogen-containing acrylic monomers, 0.01-0.05 parts of chain transfer agents and 0.05-1 parts of polymerizable photoinitiators are partially polymerized under ultraviolet light. More preferably, in the above components, the content of the polymerizable photoinitiator is 0.3-1 parts.

[0021] The polymerizable photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, a,a-dimethoxy-a-phenyl acetophenone, and benzil dimethyl ether.

[0022] The acrylic acid ester monomer having 4-8 carbon atoms may be at least one or more of butyl acrylate, n-hexyl acrylate, n-octyl acrylate, and isooctyl acrylate. Such monomers have a low Tg, can reduce the storage modulus at low temperatures, and increase the flexibility of the film.

[0023] The acrylic acid ester monomer with 8-17 carbon atoms is at least one of isodecyl acrylate, dodecyl acrylate, and heptadecyl acrylate. Such acrylic acid esters have a long chain length. By selecting long-chain acrylic acid ester monomers, the storage modulus at low temperature can be reduced and the molecular weight of the film can be increased. Long-chain acrylic acid esters can play an "internal plasticizing" role due to their long side chains, significantly reducing the low-temperature storage modulus. However, if too much long-chain acrylic acid ester monomer is added, the peeling force on the substrate will be reduced.

[0024] The addition of hydroxy acrylate monomer can increase the cohesive property of the film and increase the peeling force on the substrate. The hydroxy acrylate monomer can be one of hydroxyethyl acrylate, hydroxybutyl acrylate, and hydroxypropyl acrylate. From the perspective of low Tg, hydroxybutyl acrylate is preferred. In terms of weight, the weight of hydroxybutyl acrylate is 5-20 parts, for example, it can be 5 parts, 6 parts, 8 parts, 10 parts, 15 parts, 18 parts, 20 parts, and specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range. The weight of the hydroxy acrylate monomer is preferably 5-14 parts. When the ratio is less than 5 parts, the cohesive property of the film is insufficient. When the ratio is higher than 14 parts, the hydroxyl monomer content is too high, the cohesive property of the film is high, but the low-temperature storage modulus will increase.

[0025] The weight percentage of the nitrogen-containing acrylic ester monomer comonomer is 0-5 parts, for example, it can be 0 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range. The addition of nitrogen-containing acrylic ester monomers can increase heat resistance at high temperatures. The nitrogen-containing acrylic ester monomer can be at least one or more of N-vinyl-2-pyrrolidone and acryloylmorpholine.

[0026] A chain transfer agent is used in the acrylic resin A to control the reaction process. The chain transfer agent includes any one of n-dodecyl mercaptan, n-octadecyl mercaptan, pentaerythritol tetrakis(3-mercaptobutyrate), and 2,4-diphenyl-4-methyl-1-pentene (AMSD), or a combination of at least two thereof. The content of the chain transfer agent is preferably 0.01-0.1 parts by weight, and more preferably 0.01-0.05 parts by weight.

[0027] The acrylate resin A also contains a polymerizable photoinitiator. The polymerizable photoinitiator and the photoinitiator C are at least one or more of 1-hydroxycyclohexyl phenyl ketone, (2,4,6-trimethylbenzoyl) diphenylphosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, a,a-dimethoxy-a-phenylacetophenone, and benzil dimethyl ether. In parts by weight, the content of the polymerizable photoinitiator is preferably 0.05-1 part, and more preferably 0.3-1 part.

[0028] The acrylate resin A is prepared by ultraviolet polymerization process, wherein 30-75 parts by weight of an acrylate monomer having 4-8 carbon atoms, 5-40 parts by weight of an acrylate monomer having 8-17 carbon atoms, 5-20 parts by weight of a hydroxy acrylate monomer, 0-5 parts by weight of a nitrogen-containing group acrylate monomer, 0.01-0.5 parts by weight of a chain transfer agent and 0.01-1 parts by weight of a polymerizable photoinitiator are partially polymerized under ultraviolet light;

[0029] Acrylate resin A partially polymerizes under a certain UV intensity. The solid content reflects the degree of polymerization. The solid content (%) calculation formula is as follows:

[0030] Solid content (%) = (M1-M2) / M1*100;

[0031] Wherein M2 is the mass of acrylate resin A after drying at 150°C for 2 hours, and M1 is the initial mass of acrylate resin A. Preferably, the solid content of the acrylate resin A is 7-25%, for example, it can be 7%, 10%, 13%, 16%, 19%, 22%, 25%, and specific values ​​between the above points. Due to space limitations and for simplicity, the present invention will no longer exhaustively list the specific points included in the range. Considering ease of coating and molecular weight. The solid content of acrylate resin A is preferably 7-20%.

[0032] The viscosity of the acrylate resin A can be measured by a viscometer at room temperature 25°C. The viscosity of the acrylate resin A at 25°C is 1500-10000cps, for example, it can be 1500cps, 2500cps, 3500cps, 4500cps, 5500cps, 6500cps, 7500cps, 8500cps, 9500cps, 1000cps and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range. The viscosity of the acrylate resin A is tested by using a rotational viscometer. Preferably, the viscosity of the acrylate resin A at 25°C is 1500-5000cps.

[0033] When the viscosity of the acrylate resin A is lower than 1500 cps, the viscosity of the acrylate resin A is too thin, and the cohesive property of the cured film is insufficient. When the viscosity of the acrylate resin A is higher than 10000 cps, the viscosity of the acrylate resin A is too thick, and it is difficult to coat.

[0034] The weight average molecular weight Mw of the acrylic resin A is 700,000-1.2 million, more preferably 800,000-1,000,000.

[0035] Preferably, the preparation method of the acrylic resin A comprises: partially polymerizing 40-70 parts of an acrylic monomer having 4-8 carbon atoms, 10-40 parts of an acrylic monomer having 8-17 carbon atoms, 5-14 parts of a hydroxy acrylic monomer, 0-3 parts of a nitrogen-containing group acrylic monomer, 0.01-0.05 parts of a chain transfer agent and 0.05-1 parts of a polymerizable photoinitiator under ultraviolet light to obtain the obtained product;

[0036] The polymerization reaction is partially polymerized under inert gas and ultraviolet irradiation; preferably, the inert gas is at least one of helium and nitrogen. Preferably, the reaction is carried out under ultraviolet irradiation.

[0037] Preferably, the wavelength of the ultraviolet irradiation is 280-420 nm, for example, it can be 280 nm, 300 nm, 320 nm, 350 nm, 380 nm, 400 nm, 420 nm, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0038] Preferably, the light intensity of the ultraviolet irradiation is 1-20 mW / cm 2 , for example, 1 mW / cm 2 , 5 mW / cm 2 、10mW / cm 2 , 15 mW / cm 2 , 20 mW / cm 2 , and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention does not exhaustively list the specific point values ​​included in the above range. Preferably, the light intensity of the ultraviolet irradiation is 1-10mW / cm 2 .

[0039] The bending-resistant acrylic film of the present invention further comprises an acrylic resin B, and the weight average molecular weight Mw of the acrylic resin B is 3000-10000, and the acrylic resin is used as a low molecular weight additive. The molecular weight distribution of the acrylic resin A is narrow and the molecular weight is high. The addition of the low molecular weight acrylic resin B can increase the molecular weight distribution of the film, making the molecular weight distribution wider, and having high cohesive properties while having low molecular weight acrylic resin B to provide viscosity properties. The weight average molecular weight Mw of the acrylic resin B can be 3000-10000. When the molecular weight is lower than 3000, it is added to the acrylic resin A, and the cohesive properties of the film deteriorate, making it difficult to pass the reliability test. When the molecular weight is higher than 10000, the compatibility with the acrylic resin A deteriorates. To balance the viscosity and cohesive properties, the molecular weight of the acrylic resin B is preferably 3000-8000, and more preferably 3500-6000. The PDI of the acrylic resin B is less than 1.5. Relative to 100 parts by weight of acrylate resin A, the added amount of acrylate resin B is 1-10 parts, more preferably 3-10 parts. When the added amount is less than 3 parts, it is difficult to improve the peeling force on the substrate. When the added ratio is higher than 10 parts, the compatibility of acrylate resin B with acrylate resin A becomes worse and the haze increases.

[0040] Acrylate resin B can be obtained by bulk polymerization, emulsion polymerization, suspension polymerization, solution polymerization and other processes. Considering the cost and process control, acrylate resin B can be synthesized by solution polymerization and UV polymerization. Considering the stability and conversion rate of the acrylate resin synthesis process, it is preferred to synthesize acrylate resin B by solution polymerization.

[0041] The acrylic resin B comprises at least one of a (meth) acrylic acid chain alkyl ester monomer, a copolymerized acrylic acid ester monomer, and a polar copolymerized monomer. The (meth) acrylic acid chain alkyl ester monomer comprises at least one of methyl methacrylate, ethyl acrylate, butyl acrylate, n-butyl methacrylate, and isobutyl acrylate. From the perspective of increasing compatibility with the acrylic resin A, the (meth) acrylic acid chain alkyl ester monomer is preferably at least one of methyl methacrylate and n-butyl methacrylate.

[0042] Preferably, the acrylate resin B comprises, by weight, 10-90 parts of (meth)acrylic acid chain alkyl ester monomers, 10-60 parts of copolymerized acrylate monomers, 0-10 parts of polar comonomers, 0.01-15 parts of chain transfer agents, and 0.01-10 parts of initiators; the acrylate resin B is synthesized by bulk polymerization, emulsion polymerization, suspension polymerization or solution polymerization process.

[0043] Most preferably, the acrylate resin B comprises, by weight, 30-70 parts of (meth)acrylic acid chain alkyl ester monomer, 20-50 parts of copolymerized acrylate monomer, 0-7 parts of polar comonomer, 3-10 parts of chain transfer agent, and 0.1-8 parts of initiator.

[0044] The acrylate resin B also contains a copolymerized acrylate monomer, and the copolymerized acrylate monomer preferably has a cyclic structure. The (meth) acrylic monomer having a cyclic structure is preferably a (meth) acrylic monomer having an alicyclic ring or an aromatic ring, and more preferably a (meth) acrylic monomer having an alicyclic ring structure. It is particularly preferred that at least one is selected from cyclohexane, dicyclopentane, isobornyl and benzene. Examples of (meth) acrylic monomers having a cyclic structure include at least one of cyclohexyl (meth) acrylate, dicyclopentenyloxyethyl (meth) acrylate, isobornyl (meth) acrylate and phenoxyethyl (meth) acrylate. In addition, the (meth) acrylic monomer having a cyclic structure in the acrylate resin B can increase the peeling force to low-polarity materials.

[0045] The acrylic resin may further include a polar comonomer, such as at least one of hydroxyethyl (meth)acrylate, (meth)acrylic acid, acrylamide, and N-vinyl-2-pyrrolidone monomers. The addition of the polar monomer can increase the compatibility with the acrylic resin A.

[0046] The glass transition temperature Tg of the acrylic resin B is preferably 30°C to 70°C, more preferably 30°C to 55°C, and most preferably, the glass transition temperature Tg of the acrylic resin B is 40°C to 50°C, and the glass transition temperature Tg is tested by differential scanning calorimetry.

[0047] In order to adjust the molecular weight of the acrylic resin B, a chain transfer agent may be used in the polymerization. Examples of chain transfer agents that can be used include compounds having a mercapto group, thioglycolic acid, derivatives thereof, 2,4-diphenyl-4-methyl-1-pentene (AMSD), and the like. Specific examples of compounds having a mercapto group include octyl mercaptan, n-dodecyl mercaptan, tert-butyl dodecyl mercaptan, and the like. Specific examples of thioglycolic acid and its derivatives include esters such as thioglycolic acid, ethyl thioglycolate, propyl thioglycolate, butyl thioglycolate, tert-butyl thioglycolate, 2-ethylhexyl thioglycolate, octyl thioglycolate, decyl acetate, dodecyl thioglycolate, ethylene glycol decyl acetate, neopentyl glycol thioglycolate, and pentaerythritol thioglycolate. Among them, examples of preferred chain transfer agents include n-dodecyl mercaptan, 2,4-diphenyl-4-methyl-1-pentene (AMSD), and AMSD is more preferred in terms of color and odor.

[0048] A conventional initiator can be used to synthesize the acrylic resin B, wherein the initiator is at least one of an organic peroxide and an azo compound. Preferably, the initiator is tert-butyl peroxybenzoate.

[0049] A solvent is used in the synthesis process of the acrylic resin B. As the solvent, hydrocarbons such as toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane can be listed; alcohols such as methanol, propanol, isopropanol, butanol, isobutanol, and diacetone alcohol; ethers such as diethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; polyols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate, and their derivatives. A suitable solvent is at least one of butyl acetate, toluene, butanone, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether. Most preferably, the solvent is one or both of toluene and ethylene glycol monomethyl ether.

[0050] The acrylate resin B is synthesized by solution polymerization, and the polymerization reaction temperature ranges from 60 to 150 degrees Celsius. The acrylate resin B is obtained by controlling the reaction conditions to obtain a resin of suitable molecular weight. During the solution polymerization process, the reaction temperature can be 60 to 150 degrees Celsius, preferably 70 to 140 degrees Celsius, and more preferably 80 to 140 degrees Celsius. The molecular weight of the acrylate resin B can also be controlled by the drop rate, monomer concentration, etc., which will not be repeated here.

[0051] In a second aspect, the present invention provides a method for preparing the bending-resistant acrylic film as described in the first aspect, the preparation method comprising:

[0052] 100 parts of acrylate resin A, 0.1-10 parts of acrylate resin B, 0.01-1 parts of photoinitiator C and 0.01-1 parts of crosslinking agent D are mixed and coated on a release film, cured, and then dried in an oven at 100-150° C. for 1-6 minutes to obtain the acrylate adhesive film.

[0053] Preferably, the release film comprises a polyethylene terephthalate release film.

[0054] Preferably, the curing comprises curing under ultraviolet light, low pressure or high pressure mercury lamp;

[0055] Preferably, the curing light intensity is 1-50 mW / cm 2 Preferably, the light intensity of the ultraviolet irradiation is 1-50mW / cm 2 , for example, 1 mW / cm 2 , 5 mW / cm 2 , 10 mW / cm 2 , 15 mW / cm2 , 20 mW / cm 2 、30 mW / cm 2 , 40mW / cm 2 , 45 mW / cm 2 , 50 mW / cm 2 , as well as specific point values ​​between the above point values, due to space limitations and for the sake of brevity, the present invention no longer exhaustively lists the specific points included in the said range.

[0056] Preferably, the total radiation energy of the curing is 1000-5000 mJ, for example, it can be 1000 mJ, 2000 mJ, 3000 mJ, 4000 mJ, 5000 mJ, and specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0057] Preferably, the drying temperature of the oven is 100-150° C., more preferably 100-130° C., and the drying time is 1-6 min, preferably 1-3 min.

[0058] The glass transition temperature Tg of the bending-resistant acrylic film is -60°C to -35°C.

[0059] In a third aspect, the present invention provides a use of the bend-resistant acrylic film as described in the first aspect in a smart phone, a tablet computer, a smart watch, a media player or a television.

[0060] Beneficial effects:

[0061] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0062] The present invention provides a bending-resistant acrylic film and a preparation method and application thereof, wherein the acrylic film has good creep recovery, excellent bending performance and good bonding effect. The conventional solution process synthesizes folded OCA, with a wide molecular weight distribution and a PDI index of generally 4-7. The UV polymerization process synthesizes folded OCA, with a narrow molecular weight distribution and a PDI of 1-1.6. The UV polymerization process has a too narrow molecular weight distribution and lacks a small molecular weight polymer to provide viscosity. The present invention increases the peeling force on the substrate by using a low Tg high molecular weight acrylic resin A and a high Tg low molecular weight acrylic resin B. The molecular weight of the low Tg high molecular weight acrylic resin A is 700,000-1.2 million, and the PDI is 1-1.6. The high Tg refers to a glass transition temperature of 30°C to 70°C. The acrylic film prepared by the present invention has a thickness of 25um, a peeling force of greater than 700gf for plain glass at room temperature for 20 minutes, and a peeling force of greater than 800gf for 50umPI film (the substrate is a 50um PET film), and has a good creep recovery effect to meet dynamic folding requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0064] Figure 1 This is the GPC spectrum of the acrylic resin A1 prepared in the present invention;

[0065] Figure 2 The DSC spectrum of the acrylic film prepared in Example 1 of the present invention;

[0066] Figure 3 The DSC spectrum of the acrylic resin B2 prepared in the present invention;

[0067] Figure 4 This is a temperature scanning storage modulus diagram of the bending-resistant acrylic film provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0068] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0069] The present invention will be further described below in conjunction with the embodiments.

[0070] (I) The experimental materials used in the embodiments and comparative examples of the present invention are as follows:

[0071] (1) Raw material manufacturers

[0072] EHA, isooctyl acrylate (Yongzheng Chemical);

[0073] BA, butyl acrylate (Yongzheng Chemical);

[0074] HBA, hydroxybutyl acrylate (Osaka Organic Chemical);

[0075] NVP, N-vinylpyrrolidone (Yongzheng Chemical);

[0076] BMA, n-butyl methacrylate (Yongzheng Chemical)

[0077] IBOMA, Isobornyl Methacrylate (Yongzheng Chemical)

[0078] IDA, isodecyl acrylate (Changxing Chemical);

[0079] LA; Lauric Acid Ester (Changxing Chemical)

[0080] HDDA, 1,6-hexanediol diacrylate (Yongzheng Chemical);

[0081] Photoinitiator 651, benzil dimethyl ether, (IGM Company);

[0082] NDM, n-dodecyl mercaptan (Aladdin);

[0083] AMSD, 2,4-diphenyl-4-methyl-1-pentene (Aladdin);

[0084] TBPB, tert-butyl peroxybenzoate (Aladdin);

[0085] Photoinitiator 184, 1-hydroxycyclohexylphenyl ketone (IGM).

[0086] (2) Preparation of Acrylate Resin A1

[0087] The raw materials for preparing acrylate resin A1 include: 59.5 parts of EHA, 10 parts of BA, 10 parts of HBA, 20 parts of IDA, 0.5 parts of NVP, 0.05 parts of 651 initiator, and 0.03 parts of NDM chain transfer agent.

[0088] The preparation method of the acrylic resin A1 comprises: adding EHA, BA, HBA, IDA, NVP, 651 and NDM into a 500 mL four-necked flask, introducing nitrogen for 20 minutes, stirring evenly, irradiating under an LED ultraviolet lamp for 4 minutes, and then introducing air for polymerization inhibition, wherein the ultraviolet lamp intensity is 10 mw / cm 2 , the acrylic resin A1 was obtained, with a viscosity of 2100 cps at 25° C., a solid content of 15%, a molecular weight of 940,000, and a PDI of 1.3.

[0089] (3) Preparation of Acrylate Resin A2

[0090] The raw materials for preparing acrylic resin A2 include: 58 parts of EHA, 10 parts of BA, 10 parts of HBA, 20 parts of LA, 2 parts of NVP, 0.05 parts of 184 initiator, and 0.03 parts of NDM chain transfer agent.

[0091] The preparation method of the acrylic resin A2 comprises: adding EHA, BA, HBA, LA, NVP, 184, and NDM into a 500 mL four-necked flask, introducing nitrogen for 20 minutes, stirring evenly, irradiating under an LED ultraviolet lamp for 4 minutes, and then introducing air for polymerization inhibition, wherein the ultraviolet lamp intensity is 10 mw / cm 2 , the acrylic resin A2 was obtained, with a viscosity of 3600 cps at 25° C., a solid content of 23%, a molecular weight of 980,000, and a PDI of 1.2.

[0092] (4) Preparation of acrylic resin A3

[0093] The raw materials for preparing acrylic resin A3 include: 53 parts of EHA, 10 parts of HBA, 35 parts of LA, 2 parts of NVP, 0.1 parts of 651 initiator, and 0.02 parts of NDM chain transfer agent.

[0094] The preparation method of the acrylic resin A3 comprises: adding EHA, HBA, LA, NVP, 651 and NDM into a 500 mL four-necked flask, introducing nitrogen for 20 minutes, stirring evenly, irradiating under an LED ultraviolet lamp for 4 minutes, and then introducing air for polymerization inhibition, wherein the ultraviolet lamp irradiation intensity is 10 mw / cm 2 The acrylic resin A3 was obtained, with a molecular weight of 890,000, a PDI of 1.4, a viscosity of 2200 cps at 25°C, and a solid content of 13%.

[0095] (5) Preparation of Acrylate Resin A4

[0096] The raw materials for preparing acrylate resin A4 include: 59.5 parts of EHA, 10 parts of BA, 10 parts of HBA, 20 parts of IDA, 0.5 parts of NVP, 0.05 parts of 651 initiator, and 0.1 parts of NDM chain transfer agent.

[0097] The preparation method of the acrylic resin A4 comprises: adding EHA, BA, HBA, IDA, NVP, 651 and NDM into a 500 mL four-necked flask, introducing nitrogen for 20 minutes, stirring evenly, irradiating under an LED ultraviolet lamp for 4 minutes, and then introducing air for polymerization inhibition, wherein the ultraviolet lamp irradiation intensity is 10 mw / cm 2 , the acrylic resin A4 was obtained, with a viscosity of 1300 cps at 25° C., a solid content of 8%, a molecular weight of 600,000, and a PDI of 1.2.

[0098] (6) Preparation of Acrylate Resin B1

[0099] In a 500 mL four-necked flask, 100 parts of toluene were weighed as a solvent, the temperature was raised to 110°C, and then nitrogen was passed for 40 minutes. 60 parts of BMA, 40 parts of IBOMA, 5 parts of AMSD, and 5 parts of TBPB were weighed, and the mixture was evenly mixed and used as a dropwise solvent. The dropwise addition speed was controlled, and the reaction was carried out for 5 hours and then kept warm for 2 hours to obtain an oligomer solution. The oligomer solution was subjected to reduced pressure distillation to remove unreacted monomers, and then dried to obtain a solid acrylic resin B1. The molecular weight of the acrylic resin was tested by GPC, and the molecular weight was 5400 and the Tg was 48°C.

[0100] (7) Preparation of Acrylate Resin B2

[0101] In a 500 mL four-necked flask, 100 parts of ethylene glycol monomethyl ether were weighed as a solvent, the temperature was raised to 110°C, and then nitrogen was passed through for 40 minutes. 60 parts of BMA, 40 parts of IBOMA, 5 parts of AMSD, and 5 parts of TBPB were weighed, and the mixture was evenly mixed and used as a dropwise solvent. The dropping speed was controlled, and the reaction was carried out dropwise for 5 hours and then kept warm for 2 hours to obtain an oligomer solution. The oligomer solution was subjected to reduced pressure distillation to remove unreacted monomers, and then dried to obtain a solid acrylic resin B2. The molecular weight of the acrylic resin was tested by GPC, and the molecular weight was 4500 and the Tg was 45°C.

[0102] (8) Preparation of Acrylate Resin B3

[0103] In a 500 mL four-necked flask, 100 parts of toluene were weighed as a solvent, the temperature was raised to 110°C, and then nitrogen was passed through for 40 minutes. 60 parts of BMA, 40 parts of IBOMA, 2 parts of AMSD, and 5 parts of TBPB were weighed, mixed evenly and used as a dropwise solvent. The dropping speed was controlled, and the reaction was carried out dropwise for 5 hours and then kept warm for 2 hours to obtain an oligomer solution. The oligomer solution was subjected to reduced pressure distillation to remove unreacted monomers, and dried to obtain a solid acrylic resin B3. The molecular weight of the acrylic resin was tested by GPC, and the molecular weight was 12000 and the Tg was 58°C.

[0104] (9) Preparation of Acrylate Resin B4

[0105] In a 500 mL four-necked flask, 100 parts of butyl acetate were weighed as a solvent, the temperature was raised to 110°C, and then nitrogen was passed through for 40 minutes. 60 parts of BMA, 40 parts of IBOMA, 2 parts of AMSD, and 5 parts of TBPB were weighed, and the mixture was uniformly mixed as a dropwise solvent. The dropwise addition speed was controlled, and the reaction was carried out for 5 hours and then kept warm for 2 hours to obtain an oligomer solution. The oligomer solution was subjected to reduced pressure distillation to remove unreacted monomers, and then dried to obtain a solid acrylic resin B4. The molecular weight of the acrylic resin was tested by GPC, and the molecular weight was 30,000 and the Tg was 64°C.

[0106] (10) Preparation of Acrylate Resin B5

[0107] In a 500 mL four-necked flask, 100 parts of ethylene glycol monomethyl ether were weighed as a solvent, the temperature was raised to 110°C, and then nitrogen was passed through for 40 minutes. 60 parts of BMA, 40 parts of IBOMA, and 5 parts of TBPB were weighed, and the mixture was uniformly mixed as a dropwise solvent. The dropwise addition speed was controlled, and the reaction was carried out for 5 hours and then kept warm for 2 hours to obtain an oligomer solution. The oligomer solution was subjected to reduced pressure distillation to remove unreacted monomers, and then dried to obtain a solid acrylic resin B5. The molecular weight of the acrylic resin was tested by GPC, and the molecular weight was 60,000 and the Tg was 70°C.

[0108] (II) Implementation Examples

[0109] Embodiment 1:

[0110] 100 parts of acrylate resin A1, 5 parts of acrylate resin B1, 0.3 parts of photoinitiator 184, and 0.06 parts of HDDA were mixed and coated on a 50um heavy release film, and then attached to a 50um light release film for curing. The curing light intensity was 5 mW / cm 2 The total curing energy is 1500mj, and the above film is dried in an oven at 120℃ for 3min.

[0111] Embodiment 2:

[0112] 100 parts of acrylate resin A2, 5 parts of acrylate resin B2, 0.3 parts of photoinitiator 184, and 0.06 parts of HDDA were mixed and coated on a 50um heavy release film, and then attached to a 50um light release film for curing. The curing light intensity was 5 mW / cm 2 The total curing energy is 1500mj, and the above film is dried in an oven at 120℃ for 3min.

[0113] The components of Examples 1-6 and Comparative Examples 1-6 are shown in Table 1 and Table 2, and the preparation method is the same as that of Example 1.

[0114] (III) Performance testing

[0115] (1) Test method

[0116] ① Haze: Using a transmittance haze meter, the prepared OCA pressure-sensitive adhesive film was cut into strips with a length of 40 mm and a width of 10 mm, and the transmittance haze was measured.

[0117] ②180° peeling force test: Cut the sample into 2.5cm wide strips and conduct the test method according to the international standard ASTMD3330 "Standard for Peel Strength Test of Pressure-Sensitive Adhesive Tapes". The test panel is SUS304 steel plate. Test method: Place the test sample at room temperature for 20 minutes before the test, and record the average adhesion required to tear the strip off the test panel, expressed in gf / 25mm.

[0118] ③ Storage modulus test: Take the PET release films on both sides of the sample prepared above, overlap the multiple film layers, obtain a sample with a thickness of about 1 mm, and cut it into a disc with a diameter of 20 mm. Use a rotational rheometer to measure the shear modulus at different temperatures. The measurement frequency is 1 Hz, and the measured shear modulus value is recorded in kPa.

[0119] ④ Creep and recovery: Take the PET release films on both sides of the sample prepared above, overlap multiple film layers, obtain a sample with a thickness of about 1mm, and cut it into a disc with a diameter of 20mm. Use a rotational rheometer to apply a stress of 10kPa, a creep time of 600s, and a recovery time of 600s. Record the deformation and recovery curves of the film during the test.

[0120] ⑤Static folding test:

[0121] A 50um substrate-free optical adhesive film is attached to a 50umPI film to form a five-layer structure of PI / OCA / PI / OCA / PI. The film is placed in an environment of 85 degrees Celsius and 80%RH for 500 hours using a homemade fixture (folding radius R=2mm) to observe whether there is any detachment from the substrate or obvious creases. If not, it is judged as passed; otherwise, it is judged as failed.

[0122] ⑥Dynamic folding test:

[0123] A 50um substrate-free optical film is attached to a 50umPI film to form a five-layer structure of PI / OCA / PI / OCA / PI. The dynamic folding tester is used for testing at a speed of 40 times / min, folding R=2mm, and folding times of 200,000 times. Observe whether there is any phenomenon of separation from the substrate or obvious creases. If there is no such phenomenon, it is judged as passed, otherwise it is judged as failed.

[0124] (2) Test results

[0125] The performance test results of Examples 1-6 are shown in Table 3:

[0126]

[0127] The performance test results of Comparative Examples 1-6 are shown in Table 4:

[0128]

[0129] In Examples 1-3, due to the use of acrylic resins with a molecular weight of 700,000 to 1,000,000, the molecular weight of acrylic resins B1 and B2 is relatively small, and the haze of the overall film is relatively small. The addition of low molecular weight substances improves the peeling force on the substrate and has a relatively small effect on the storage modulus at low temperatures. Example 4 uses acrylic resin A4 with a molecular weight lower than 700,000, and the overall cohesive performance of the film decreases, so the creep recovery performance and room temperature storage modulus decrease, and the static and dynamic folding performance are affected. In Examples 5 and 6, more low molecular weight resins are added, and the compatibility becomes poor, so the haze of the film increases.

[0130] In Comparative Examples 1-2, no low molecular weight resin is used in acrylate resin A1 and acrylate resin A2, and the haze is low, but the peeling force on the substrate is low, and the static folding and dynamic folding performances fail. In Comparative Examples 3-5, acrylate resins B3 and B4 are added. Since the molecular weight of B3 and B4 resins is high, the compatibility with acrylate resin A deteriorates, so the haze increases, and the poor compatibility causes phase separation between acrylate resin A, so the effect of increasing the peeling force is not obvious. In Comparative Example 6, the molecular weight of acrylate resin A4 is low, and the molecular weight of acrylate resin B5 is too large, so the overall performance is not good.

[0131] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the protection scope of the technical solutions of the embodiments of the present invention.

Claims

1. A bending-resistant acrylic film, characterized in that: In parts by weight, it includes 100 parts of acrylate resin A, 0.1-10 parts of acrylate resin B, 0.01-1 parts of photoinitiator C, and 0.01-1 parts of crosslinking agent D; The weight average molecular weight Mw of the acrylate resin A is 800,000-1,000,000; the solid content of the acrylate resin A is 7-25%, and the viscosity is 1,500-10,000 cps; the weight average molecular weight Mw of the acrylate resin B is 3,000-8,000, and the glass transition temperature Tg of the acrylate resin B is 30-55° C.; the crosslinking agent D is at least one of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate, and bifunctional aliphatic polyurethane acrylate; In parts by weight, the acrylic resin A comprises 30-75 parts of an acrylic monomer having 4-8 carbon atoms, 5-40 parts of an acrylic monomer having 8-17 carbon atoms, 5-20 parts of a hydroxy acrylic monomer, 0-5 parts of a nitrogen-containing acrylic monomer, 0.01-0.5 parts of a chain transfer agent and 0.01-1 parts of a polymerizable photoinitiator; wherein in the acrylic resin A, the acrylic monomer having 4-8 carbon atoms is at least one or more of butyl acrylate, n-hexyl acrylate, n-octyl acrylate and isooctyl acrylate; the acrylic monomer having 8-17 carbon atoms is at least one or more of isodecyl acrylate, dodecyl acrylate and heptadecyl acrylate; the hydroxy acrylic monomer is at least one of hydroxyethyl acrylate, hydroxypropyl acrylate and hydroxybutyl acrylate. The above; the nitrogen-containing group acrylate monomer is at least one of N-vinyl-2-pyrrolidone and acryloylmorpholine; the chain transfer agent includes any one of n-dodecyl mercaptan, n-octadecyl mercaptan or tetrakis (3-mercaptobutyric acid) pentaerythritol ester, 2,4-diphenyl-4-methyl-1-pentene or a combination of at least two; the polymerizable photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, a, a-dimethoxy-a-phenyl acetophenone, and benzil dimethyl ether; the acrylate resin A is prepared by ultraviolet polymerization, wherein the wavelength of the ultraviolet irradiation is 280-420nm, and the light intensity of the ultraviolet irradiation is 1-20mW / cm 2 ; The acrylic resin B contains at least one or more of a (meth)acrylic acid chain alkyl ester monomer, a copolymerized acrylate monomer, and a polar copolymerized monomer; the (meth)acrylic acid chain alkyl ester monomer contains at least one or more of methyl methacrylate, ethyl acrylate, butyl acrylate, n-butyl methacrylate, and isobutyl acrylate; the polar copolymerized monomer includes at least one or more of hydroxyethyl (meth)acrylate, (meth)acrylic acid, acrylamide, and N-vinyl-2-pyrrolidone monomers.

2. The bending-resistant acrylic film according to claim 1, characterized in that: The photoinitiator C is at least one or more of 1-hydroxycyclohexyl phenyl ketone, (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 2-hydroxy-2-methyl-1-phenyl-1-propanone, a,a-dimethoxy-a-phenyl acetophenone, and benzil dimethyl ether.

3. The bending-resistant acrylic film according to claim 1, characterized in that: The acrylic resin B further comprises a chain transfer agent and an initiator; the chain transfer agent comprises at least one of a compound having a mercapto group and 2,4-diphenyl-4-methyl-1-pentene; the initiator is at least one of an organic peroxide and an azo compound.

4. The bending-resistant acrylic film according to claim 3, characterized in that: In parts by weight, the acrylate resin B comprises 10-90 parts of (meth)acrylic acid chain alkyl ester monomers, 10-60 parts of copolymerized acrylate monomers, 0-10 parts of polar comonomers, 0.01-15 parts of chain transfer agents, and 0.01-10 parts of initiators; the acrylate resin B is synthesized by bulk polymerization, emulsion polymerization, suspension polymerization or solution polymerization process.

5. The bending-resistant acrylic film according to claim 4, characterized in that: The acrylic resin B is synthesized by solution polymerization, the polymerization reaction temperature range is 60-150 degrees Celsius, and the reaction solvent is at least one of ethyl acetate, butyl acetate, toluene, xylene, butanone, methyl isobutyl ketone, ethylene glycol monomethyl ether, propylene glycol methyl ether, and diethylene glycol dimethyl ether.

6. A method for preparing the bending-resistant acrylic film according to any one of claims 1 to 5, characterized in that: The preparation method comprises: mixing acrylate resin A, acrylate resin B, photoinitiator C and crosslinking agent D, degassing the mixture, coating the mixture on a release film, UV curing the mixture, and drying the mixture in an oven at 100-150° C. for 1-6 minutes to obtain the acrylate adhesive film.

7. A bend-resistant acrylic film as described in any one of claims 1 to 5 or a bend-resistant acrylic film prepared by the preparation method as described in claim 6, which is used in a smart phone, a tablet computer, a smart watch, a media player or a television.

Citation Information

Patent Citations

  • Acrylic-based flexible assembly layer

    CN108064202A

  • Adhesive composition for optical use and the adhesive film for optical use

    KR1020170115227A